Implementasi Alat Bantu Komunikasi Menggunakan Pergerakan Bola Mata berbasis Electrooculography dengan Metode Derivative Function - Hafiz Nul Hakim; Rizal Maulana; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disease that causes humans to not be able to move parts of their body and can even cause conditions of speech difficulties. The cause of this disease is genetic and environmental factors. In the early stages, ALS sufferers's muscle will weaken in one of the legs or hands. Muscle weakness slowly spreads such as the neck muscles, back muscles, muscles needed to talk, breathe, swallow food and other muscles that will progressively suffer from paralysis. But the bladder muscles, eye and sphinfer muscles are declared free of this disease (Palmowski, et al., 1995). Electrodes, signal conditioning circuits, arduino uno microcontrollers with bluetooth module, and smartphones can detect eye movements and implement them to sufferers to be able to communicate with people around them.The signal conditioning circuit includes the instrumentation amplifier circuit and the low pass filter. Eye movements can be classified into five movement there are front, right, left, top and bottom. From eye movements, it can be used as a command to communicate the needs of sufferers with those around them via a smartphone, so bluetooth communication is needed to send data in microcontroller to the smartphone. The system has been tested 10 times and has an accuracy of 80%.